Comic books produced by peasant and indigenous students: a study from the cultural-historical theory (Revista NUPEART, 2024)
We understand that the Cultural-Historical Theory seeks to elaborate teaching instruments that differ from traditional teaching, since it enables individuals to appropriate theoretical knowledge so that, in fact, psychic development occurs, by means of historical and cultural elements. Its objective is to identify the contributions of Comic Books as a didactic and pedagogical resource for peasant students at a public Brazilian university. The methodology is the Didactic-Training Experiment and the observation of the Comics classes held with peasant students. The experiment developed allowed us to understand that the learning developed throughout the study activity proposed to the students (comic books production) became efficient, as they were able to develop steps of this activity with more autonomy, without the help of the subject teacher. This reveals that they were able (some with more ease, others not so much) to form concepts, promoting theoretical thinking and, consequently, to transform their realities from the understanding they have of the essence of the Brazilian countryside (and not only its appearance), as was evident in their stories.
Keywords: Comic Books; Rural Education; Developmental Teaching